The lava jato case in Peru: description, appraisal and enforcement - Guimaray Mori, Erick (2018)
Complex criminal acts do not only are that way due to their coordination and intervention methods, but also because of the political and economic power that their protagonists attend. The Peruvian case called Lava Jato is not only important because of it White Collar nature, but also because of the economic and political consequences.The complexity of a judicial case is measured by its evidence and its implications, therefore, it is necessary to split the main elements of the plot, link them with the criminality that supports it and interpret our criminal rules in a coherent and sustainable manner over time. The importance and valuation of the unfair of the extraneus in cases of great corruption is a good example of that task.